2022
DOI: 10.3390/cancers14112612
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of HPV Tests in Latin America: What We Learned; What Should We Have Learned, and What Can We Do Better?

Abstract: Cervical cancer is caused by HPV. Although it is the fourth most common type of cancer diagnosed and the fourth cause of cancer death, cervical cancer is nearly completely preventable because of the vaccination and screening available. The present review aims to map the initiatives conducted to implement or evaluate the implementation of HPV testing in Latin American countries. We performed the review by searching on PubMed in the English language and on grey literature, as most of the information about the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…This study identified several areas for improvement at each sub-process or level of CC prevention program in Mexico, which have been affected by disruptions of preventive health and cancer care services because of the COVID-19 pandemic, in order to achieve the WHO goal of eliminating CC by 2030. Considering the cost of human life and suffering, implementing proper management of CC prevention programs should be a top priority for decision-makers and policy makers of CC prevention systems in all LAC countries to improve the performance indicators ( 52 , 53 ), owing to the high prevalence of CC, the female cancer with the greatest preventive potential given its natural history.…”
Section: Discussionmentioning
confidence: 99%
“…This study identified several areas for improvement at each sub-process or level of CC prevention program in Mexico, which have been affected by disruptions of preventive health and cancer care services because of the COVID-19 pandemic, in order to achieve the WHO goal of eliminating CC by 2030. Considering the cost of human life and suffering, implementing proper management of CC prevention programs should be a top priority for decision-makers and policy makers of CC prevention systems in all LAC countries to improve the performance indicators ( 52 , 53 ), owing to the high prevalence of CC, the female cancer with the greatest preventive potential given its natural history.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is the fourth most diagnosed cancer, and the fourth leading cause of cancer death, cervical cancer is almost completely preventable due to the available vaccination and screening [33,34]. In Brazil, cervical cancer is the third most common type of cancer, and the most likely among women in the north of the country [35].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the Papillomavirus Family recorded more than four hundred types; Some subtypes have been discovered in different human anatomic sites. And caused proliferative lesions on the skin and mucosa, or in other places, such as the penile, anal, oropharyngeal, vulvar, and uterine cervix regions [4]. And the most generally sexually transmitted human virus and perhaps the cause of a great number of cancers in both men and women, in a lot of areas of body tissues [5].…”
Section: Introductionmentioning
confidence: 99%